Age-related immune response to experimental infection with Eimeria ninakohlyakimovae in goat kids. (June 2018) - Matos, L.; Muñoz, M.C.; Molina, J.M.; Rodríguez, F.; Pérez, D.; López, A.M.; Hermosilla, C.; Taubert, A.; Ruiz, A.
Abstract: Both the immune response developed in ruminants against Eimeria spp. and the ability to bear patent infections seems to be dependent on the age of the host. In the present study we have evaluated the influence of the age in the development of protective immune responses against Eimeria ninakohlyakimovae . For this purpose, 3, 4 and 5-week-old goat kids were infected with sporulated oocysts and subjected to a homologous challenge 3 weeks later. Goat kids primary infected at 6, 7 and 8 weeks of age served as challenge controls, and uninfected animals were used as negative controls. The protective immunity was assessed by clinical, haematological, parasitological, immunological and pathological parameters. Altogether, the results demonstrate that goat kids of either 3, 4 or 5 weeks of age are able to develop patent infections and immunoprotective responses against E. ninakohlyakimovae, as all age groups: (i) released significantly less oocysts after challenge, which was associated to milder clinical signs; (ii) displayed a local immune response, with significant increase of numerous cellular populations; and (iii) had increased levels of IgG and IgM, and mainly of local IgA. Nevertheless, detailed analysis of the data showed some differences between the three age groups, related both to the Eimeria infection outcome and the resulting immune response, suggesting that youngest goat kids are not fully immunocompetent. This finding may be of interest for the design of immunoprophylactic approaches and/or prophylactic/methaphylactic treatments against goat coccidiosis. Highlights: Protective responses against E. ninakholyakimovae in goat kids are age-related. Effector cell-mediated innate immune reactions are increased in younger goat kids. Effector cell-mediated acquired immune reactions are decreased in younger goat kids. Kids younger than 3 weeks may be not fully competent against Eimeria infections. Age might be considered in treatment and immunoprophylaxis of ruminant eimeriosis.